Studies into the occurrence of alpha-onocerin in restharrow - Hayes, Steven Paul (2013)
With the increasing evidence of climate change in the coming decades, adaptive mechanisms present in nature may permit crop survival and growth on marginal or saline soils and is considered an important area of future research. Some subspecies of Restharrow; O. repens subsp. maritima and O. reclinata have developed the remarkable ability to colonise sand dunes, shingle beaches and cliff tops. α-onocerin is a major component within the roots of Restharrow (Ononis) contributing up to 0.5% dry weight as described by Rowan and Dean (1972b). The ecological function of α-onocerin is poorly understood, with suggestions that it has waterproofing properties, potentially inhibiting the flow of sodium chloride ions into root cells, or preventing desiccation in arid environments. The fact that alpha-onocerin (a secondary plant metabolite) biosynthesis has evolved a number of times in distantly related taxa; Club mosses, Ferns and Angiosperms, argues for a relatively simple mutation from non-producing antecedents. No direct research has been reported to have investigated the biosynthetic mechanism towards α-onocerin synthesis via a squalene derived product originally characterised by Dean, and Rowan (1972a). A bi-cyclisation event of 2,3;22,23-dioxidosqualene by an oxidosqualene cyclase, may provide plants with an alternative mechanism for synthesising a range of triterpene diol products via alpha-onocerin (Dean, and Rowan, 1972a). This mechanistic possibility presented the opportunity to investigate the biosynthesis of α-onocerin using a multi-disciplinary approach. This thesis presents supporting data, that α-onocerin is a derivative of 2,3;22,23-dioxidosqualene via an oxidosqualene cyclase. Genetic markers were developed for Ononis versions of squalene cyclase, squalene epoxidase and a putative oxidosqualene cyclase. It was determined that squalene epoxidase; At4g37760 (SQE3), from A. thaliana showed the highest level of amino acid sequence conservation with the O. spinosa version. SQE3 is known to cyclise 2,3;22,23-dioxidosqualene (Rasbery et al., 2007). Based on amino acid sequence alignments and predictive protein modelling a partial putative oxidosqualene cyclase isolated from O. repens III subsp. maritima is likely to be an Ononis version of β-amyrin synthase rather than a multifunctional oxidosqualene cyclase. Further functional characterisation studies are needed. Methods were developed for analysing the transcriptome and metabolome in Restharrow which will aid future functional characterisation studies. Within O. spinosa root SQE3 was highly expressed. In contrast SQE3 was expressed at low levels in O. spinosa leaf and O. pusilla root and leaf. This data was supported by metabolomic profiling of five species of Restharrow; O. spinosa, O. repens, O. repens subsp. maritima, O. pusilla and O. rotundifolia. Triterpenes α-onocerin and 2,3;22,23-dioxidosqualene were not present in O. rotundifolia and O. pusilla. Where 2,3;22,23-dioxidosqualene was present in plant extracts, α-onocerin accumulation was also detected. O. pusilla and O. spinosa can be utilised for studying the occurrence of alpha-onocerin within plants. The data presented in this thesis provides the necessary background information providing targets for functional expression studies of squalene epoxidases and oxidosqualene cyclases from Restharrow. In summary the results in this thesis support the hypothesis proposed by Dean and Rowan (1971). There is good evidence to suggest the ability of Restharrow to cyclise alpha-onocerin, may be dependant on the availability of 2,3;22,23-dioxidosqualene as the primary precursor. This was shown in development, tissue specific, ecotype and cell free enzyme analytical chemistry assays. There was little evidence to suggest a single specific oxidosqualene cyclisation event was primarily responsible for alpha-onocerin biosynthesis. The work also presents evidence to suggest that differences in the squalene epoxdiase sequence and transcription signals may affect the plants ability to cyclise alpha-onocerin. This may have ecological implications and allow plants to adapt to their environment by providing and alternative route to biosynthesising membrane constituents via an alternative substrate specific mechanism.